Assessing Mitochondrial Selective Autophagy in the Nematode Caenorhabditis elegans - Palikaras, K.; Tavernarakis, N. (Methods Mol Biol, 2017)
Eukaryotic cells heavily depend on ATP generated by oxidative phosphorylation (OXPHOS) within mitochondria. Besides being the main suppliers of cell's energy, mitochondria also provide an additional compartment for a wide range of cellular processes and metabolic pathways. Mitochondria constantly undergo fusion/fission events and form a mitochondrial network, which is a highly dynamic, tubular structure allowing for rapid and continuous exchange of genetic material, as well as, targeting dysfunctional mitochondria for degradation through mitochondrial selective autophagy (mitophagy). Mitophagy mediates the elimination of damaged and/or superfluous organelles, maintaining mitochondrial and cellular homeostasis. In this chapter, we present two versatile, noninvasive methods, developed for monitoring in vivo mitophagy in C. elegans. These procedures enable the assessment of mitophagy in several cell types during development or under stress conditions. Investigating the role of mitophagy at the organismal level is essential for the development of therapeutic interventions against age-related diseases.
Palikaras, KonstantinosTavernarakis, NektariosengMethods Mol Biol. 2017;1567:349-361. doi: 10.1007/978-1-4939-6824-4_21.
Keywords: *Ageing; *Autophagosome; *Autophagy; *Caenorhabditis elegans; *DsRed; *Fluorescent microscopy; *Green Fluorescent Protein (GFP); *Lysosomes; *Mitochondria; *Mitophagy; *mtRosella; Animals; Animals, Genetically Modified; Autophagosomes/metabolism; Biological Assay/*methods; Caenorhabditis elegans/*metabolism; Data Interpretation, Statistical; gene expression; Genes, Reporter; Heat-Shock Response; Image Processing, Computer-Assisted; Lysosomes/metabolism; Microscopy, Fluorescence; Mitochondria/genetics/*metabolism; Molecular Imaging/methods; Oxidative Stress